IoT based smart irrigation control and monitoring system - Abu Hassan, Omar; Nordin, Noorzulaika; Norjali, Rasida; Lam, Hong Yin; Sim, Sy Yi; Zambri, Nor Aira (FAZ Publishing, 2020)
The "Internet of things" (IoT) has been rapidly developed and applied to the various sector including automotive, manufacture, industrial, and many more. IoT also refers to connecting to another device through a network without any interactions from the human. In this project, the idea is to design and develop an irrigation system that can be control and monitor by using a mobile phone. The purpose of this work is to help agriculture sector in maintaining the moisture of their plantation automatically. The design system should be able to monitor and controller the watering system automatically by detecting the level of moisture in the soil. At the end of the project, smart irrigation system, with an IoT functionality, is successfully designed and tested. Earlier testing provides some promising result, with system can be either automatically controlled or manually control, remotely using smartphone.